Study theEffects of Glutathione (GSH) on Blood Glucose Level in Diabetic Male Mice - Al Kadhem, Niyaf Nidhal; Al Ani, Nabeel K; Pasini, Maria (Al-Nahrain Journal of Science, 2018)
Investigated effects of daily injections intra venially (IV) of glutathione (GSH) (11.37 mg/mice)forthe periods 10 and 20 days,for healthy mice and diabetic male micecompared them with control group and diabetic non treated male mice, blood sugar was testedfor fasting mice, induced diabetic, to study the glutathione daily injections e3.ffects on the blood sugar level, total glutathione assay in different body organs and finally study the expression level of the glutathione redox system enzymes glutathione reductase (GR) and glutathione peroxidase (GPx) in pancreas, spleen, testis, and epididymus by the Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). The experiment outcomes for the glutathione daily injection for the diabetic induced male mice high sugar level significantly decreased. Moreover, the oxidative stress in diabetic male mice leads to depletion of total glutathione level in body organs. Finally, Diabetes causes high oxidative stress in male mice which leads to increase expressions of antioxidants enzymes GR and GPx in pancreas, epididymus and testis.